2009
DOI: 10.1007/s10461-009-9643-x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of the Effects of Housing Assistance on the Health and Risk Behaviors of Homeless and Unstably Housed People Living with HIV

Abstract: Homelessness affects HIV risk and health, but little is known about the longitudinal effects of rental assistance on the housing status and health of homeless and unstably housed people living with HIV/AIDS. Homeless/unstably housed people living with HIV/AIDS (N = 630) were randomly assigned to immediate Housing Opportunities for People with AIDS (HOPWA) rental assistance or customary care. Self-reported data, CD4, and HIV viral load were collected at baseline, 6, 12, and 18 months. Results showed that housin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
197
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(206 citation statements)
references
References 32 publications
3
197
0
2
Order By: Relevance
“…Similarly, in a recent study comparing homeless and unstably housed persons living with HIV/AIDS who were randomized to either rental assistance or customary care, the limited ability to detect meaningful between-group changes over time using intent-to-treat analyses was attributed to the attainment of stable housing among participants. 33 For their study, Wolitski et al (2010) observed that 51% of participants in the comparison condition obtained stable housing during the 18-month follow-up period. 33 Finally, we used self-report to assess hospitalizations, emergency room visits, psychiatric visits, and non-psychiatric medical professional visits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a recent study comparing homeless and unstably housed persons living with HIV/AIDS who were randomized to either rental assistance or customary care, the limited ability to detect meaningful between-group changes over time using intent-to-treat analyses was attributed to the attainment of stable housing among participants. 33 For their study, Wolitski et al (2010) observed that 51% of participants in the comparison condition obtained stable housing during the 18-month follow-up period. 33 Finally, we used self-report to assess hospitalizations, emergency room visits, psychiatric visits, and non-psychiatric medical professional visits.…”
Section: Discussionmentioning
confidence: 99%
“…33 For their study, Wolitski et al (2010) observed that 51% of participants in the comparison condition obtained stable housing during the 18-month follow-up period. 33 Finally, we used self-report to assess hospitalizations, emergency room visits, psychiatric visits, and non-psychiatric medical professional visits. In contrast, other studies have used administrative databases to obtain health care utilization data for their participants.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Increasingly, researchers have begun to assess how these structural factors are associated with HIV/AIDS risk behaviors in order to create multilevel HIV/STI prevention programs that go beyond traditional, individual-level behavior change efforts. [12][13][14][15][16] Given our interest in understanding how neighborhood disadvantage may influence youth HIV/AIDS risk, we focused on youth condom use across adolescence as it is the only reproductive health technology that serves as a barrier method against HIV/STI infection during youth's exploration of their sexuality. Specifically, we examined how neighborhood disadvantage was associated with condom use in a sample of African American youth followed over the high school years.…”
mentioning
confidence: 99%
“…Several years later, Wolitski et al (2010) published a report of a multi-site randomized controlled trial involving homeless or precariously housed HIV positive adults. The effects of rental housing assistance and case management as the intervention were compared to participants receiving usual housing services and case management referral from agencies involved with the study.…”
Section: Housing First As a Structural Intervention To Decrease Unpromentioning
confidence: 99%